Ionic mechanisms of disopyramide prolonging action potential duration in human-induced pluripotent stem cell-derived cardiomyocytes from a patient with short QT syndrome type 1 - Lan, Huan; Xu, Qiang; El-Battrawy, Ibrahim; Zhong, Rujia; Li, Xin; Lang, Siegfried; Cyganek, Lukas; Borggrefe, Martin; Zhou, Xiao-Bo; Akın, Ibrahim (Frontiers in pharmacology, 2020)
Short QT syndrome (SQTS) is associated with tachyarrhythmias and sudden cardiac death. So far, only quinidine has been demonstrated to be effective in patients with SQTS type 1(SQTS1). The aim of this study was to investigate the mechanisms of disopyramide underlying its antiarrhythmic effects in SQTS1 with the N588K mutation in HERG channel. Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from a patient with SQTS1 and a healthy donor, patch clamp, and calcium imaging measurements were employed to assess the drug effects. Disopyramide prolonged the action potential duration (APD) in hiPSC-CMs from a SQTS1-patient (SQTS1-hiPSC-CMs). In spontaneously beating SQTS1-hiPSC-CMs challenged by carbachol plus epinephrine, disopyramide reduced the arrhythmic events. Disopyramide enhanced the inward L-type calcium channel current (ICa-L), the late sodium channel current (late INa) and the Na/Ca exchanger current (INCX), but it reduced the outward small-conductance calcium-activated potassium channel current (ISK), leading to APD-prolongation. Disopyramide displayed no effects on the rapidly and slowly activating delayed rectifier and ATP-sensitive potassium channel currents. In hiPSC-CMs from the healthy donor, disopyramide reduced peak INa, ICa-L, IKr, and ISK but enhanced late INa and INCX. The results demonstrated that disopyramide may be effective for preventing tachyarrhythmias in SQTS1-patients carrying the N588K mutation in HERG channel by APD-prolongation via enhancing ICa-L, late INa, INCX, and reducing ISK.
Gesehen am 30.09.2024